Sex-dependent adaptive changes in serotonin-1A autoreceptor function and anxiety in Deaf1-deficient mice. Issue 1 (December 2016) - Luckhart, Christine; Philippe, Tristan; Le François, Brice; Vahid-Ansari, Faranak; Geddes, Sean; Béïque, Jean-Claude; Lagace, Diane; Daigle, Mireille; Albert, Paul
Abstract The C (-1019) G rs6295 promoter polymorphism of the serotonin-1A (5-HT1A) receptor gene is associated with major depression in several but not all studies, suggesting that compensatory mechanisms mediate resilience. The rs6295 risk allele prevents binding of the repressor Deaf1 increasing 5-HT1A receptor gene transcription, and the Deaf1-/- mouse model shows an increase in 5-HT1A autoreceptor expression. In this study, Deaf1-/- mice bred on a mixed C57BL6-BALB/c background were compared to wild-type littermates for 5-HT1A autoreceptor function and behavior in males and females. Despite a sustained increase in 5-HT1A autoreceptor binding levels, the amplitude of the 5-HT1A autoreceptor-mediated current in 5-HT neurons was unaltered in Deaf1-/- mice, suggesting compensatory changes in receptor function. Consistent with increased 5-HT1A autoreceptor functionin vivo, hypothermia induced by the 5-HT1A agonist DPAT was augmented in early generation male but not female Deaf1-/- mice, but was reduced with succeeding generations. Loss of Deaf1 resulted in a mild anxiety phenotype that was sex-and test-dependent, with no change in depression-like behavior. Male Deaf1 knockout mice displayed anxiety-like behavior in the open field and light-dark tests, while female Deaf1-/- mice showed increased anxiety only in the elevated plus maze. These data show that altered 5-HT1A autoreceptor regulation in male Deaf1-/- mice can be compensated for by generational adaptation of receptor response that may help to normalize behavior. The sex dependence of Deaf1 function in mice is consistent with a greater role for 5-HT1A autoreceptors in sensitivity to depression in men.